2010
DOI: 10.1209/0295-5075/92/47009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonequilibrium phonons on hot-electron spin relaxation in n-type GaAs quantum wells

Abstract: We have studied the effect of nonequilibrium longitudinal optical phonons on hot-electron spin relaxation in n-type GaAs quantum wells. The longitudinal optical phonons, due to the finite relaxation rate, are driven to nonequilibrium states by electrons under an in-plane electric field. The nonequilibrium phonons then in turn influence the electron spin relaxation properties via modifying the electron heating and drifting. The spin relaxation time is elongated due to the enhanced electron heating and thus the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, by considering that u η in both conduction and valence bands are along the θ k = 0 direction, it is shown that the hottest phonons appear in the direction parallel to u η and the coldest phonons antiparallel to u η . This phenomenon is also shown in semiconductors under static electric field [91]. It can be understood from the generation rate of phonons due to the electron-phonon scattering (equation (17)) after the establishment of the drifted Fermi distribution of electrons.…”
Section: Dynamics Of Phononsmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, by considering that u η in both conduction and valence bands are along the θ k = 0 direction, it is shown that the hottest phonons appear in the direction parallel to u η and the coldest phonons antiparallel to u η . This phenomenon is also shown in semiconductors under static electric field [91]. It can be understood from the generation rate of phonons due to the electron-phonon scattering (equation (17)) after the establishment of the drifted Fermi distribution of electrons.…”
Section: Dynamics Of Phononsmentioning
confidence: 80%
“…This phenomenon is also shown in semiconductors under static electric field. 82 It can be understood from the generation rate of phonons due to the electron-phonon scattering [Eq. (17)] after the establishment of the drifted Fermi distribution of electrons.…”
Section: Dynamics Of Phononsmentioning
confidence: 99%
“…The spin-flip terms correspond to the Elliot-Yafet and/or Bir-Aronov-Pikus mechanisms. Detailed expressions of these terms in the kinetic spin Bloch equations depend on the band structures, doping situations and dimensionalities [9] and can be found in the literature for different cases, such as intrinsic quantum wells [18], n-type quantum wells without [21,28,29,30,31] and with [22,32,33,34] electric field, p-type quantum wells [35,36,37], quantum wires [38,39], quantum dots [40] and bulk materials [41] in the spacial uniform case and quantum wells in spacial non-uniform case [23,24,42,43]. By numerically solving the kinetic spin Bloch equations with all the scattering explicitly included, one is able to obtain the time evolution and/or spacial distribution of the density matrices, and hence all the measurable quantities, such as mobility, diffusion constant, optical relaxation/dephasing time, spin relaxation/dephasing time, spin diffusion length, as well as hot-electron temperature, can be determined from the theory without any fitting parameters.…”
Section: Kinetic Spin Bloch Equationsmentioning
confidence: 99%